1994
DOI: 10.1136/jmg.31.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism with a normal cell line and an autosomal structural rearrangement.

Abstract: Over three decades, 12 cases of mosaicism for an autosomal rearrangement were recognised in the major

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 34 publications
1
36
0
3
Order By: Relevance
“…To our knowledge, only 23 such cases have been reported. They include mosaicism for duplications [Harrod et al, 1980;Cantu and Ruiz, 1986;Serotkin et al, 1988;Blouin et al, 1991;Jewell et al, 1992;Dixon et al, 1993;Gardner et al, 1994], deletions [Wilson and Lin, 1988;Ritter et al, 1990;Patel et al, 1992;D'Alessandro et al, 1992;Finucane et al, 1993;Gordon et al, 1993;Sybert, 1994], insertions [Nielsen et al, 1978], isochromosomes [Robinow et al, 1989;Stanley et al, 1993;Sybert, 1994], and derivative chromosomes [Tsien et al, 1991;Powell et al, 1991;Pelligrino et al, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 23 such cases have been reported. They include mosaicism for duplications [Harrod et al, 1980;Cantu and Ruiz, 1986;Serotkin et al, 1988;Blouin et al, 1991;Jewell et al, 1992;Dixon et al, 1993;Gardner et al, 1994], deletions [Wilson and Lin, 1988;Ritter et al, 1990;Patel et al, 1992;D'Alessandro et al, 1992;Finucane et al, 1993;Gordon et al, 1993;Sybert, 1994], insertions [Nielsen et al, 1978], isochromosomes [Robinow et al, 1989;Stanley et al, 1993;Sybert, 1994], and derivative chromosomes [Tsien et al, 1991;Powell et al, 1991;Pelligrino et al, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…There have only been 2 previously reported cases of t(11; 22) mosaicism [Gardner et al,1994;Kurahashi et al, 2000b]. The first published case was the grandmother of a patient with Emanuel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The first published case was the grandmother of a patient with Emanuel syndrome. Her karyotype was 46,XX/46,XX,t(11; 22) with 38% normal cells and 62% cells with the translocation [Gardner et al, 1994]. The second published case was a female with the karyotype 46,XX/46,XX,t(11; 22) with 20% normal cells and 80% cells with the translocation [Kurahashi et al, 2000b].…”
Section: Discussionmentioning
confidence: 99%
“…3,8 Until now, only 11 studies have described germinal mosaicism involving structural chromosomal aberration. [9][10][11][12][13][14][15][16][17][18][19] Indeed, five studies reported structural abnormality with a maternal mosaicism origin. 9,10,11,18,19 Engel et al 9 reported a familial pseudodicentric chromosome (5;21) occurring on maternal germline mosaicism as revealed by microsatellite marker analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Germinal mosaicism is independent of maternal age. 2 Few studies in literature have described germinal mosaicism corresponding essentially to aneuploidies and structural chromosomal aberrations including mostly isochromosomes and deletions [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (for review, see Röthlisberger and Kotzot 20 ).…”
Section: Introductionmentioning
confidence: 99%